Direct hydrothermal synthesis of mesoporous Sn-SBA-15 materials under weak acidic conditions - Shah, P.; Ramaswamy, A. V.; Lazar, Karoly; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2007)
A direct synthetic route for the preparation of Sn-SBA-15 materials with n(Si)/n(Sn), ratios ranging from 100 to 10 under milder acidic conditions than normally employed for the preparation of Si-SBA-15 is reported. The changes in the pH conditions of the gel were made through an adjustment of the molar ratio of n(H2O) to n(HCl) (< 1 pH < 2) during preparation. The samples prepared under three different acidic conditions have been characterized by various techniques. An expansion of the lattice (powder XRD) and an increase in mesopore area (low temperature N-2 adsorption) indicate that the hexagonal structure of the SBA- 15 is maintained with no loss of long range ordering. The UV-vis reflectance spectra of Sn-SBA-15 samples show the presence of Sn4+ ions both in tetrahedral and octahedral environment. Si-29 MAS NMR spectra of samples prepared under an intermediate acid condition show the presence Of Q(3) and Q(4) species. Their ratio increases with a decrease in tin content. The presence of Si in (2Si, 2Sn) i.e., Q(2) environment may point to incorporation of considerable Sn4+ ions in tetrahedral positions. Sn-Mossbauer spectroscopic studies reveal that Sn2+ species form upon reductive treatments and can probably be stabilized in the pore wall upon reoxidation. This to some extent is an indication of the formation and stabilization of Si-O-Sn-O-Si linkages in Sn-SBA-15. A progressive increase in the pH of the medium (increasing the n(H2O) to n(HCl), ratio) results in the location of Sn4+ ions, (a) at the surface of the mesopores (surface of the corona region) as a thin film of SnO2 or small aggregates (loss in mesopore area) depending on the concentration of Sn; (b) at the walls of the mesopore structure, substituting Si4+ ions (some lattice expansion and tetrahedral Sn4+ ions); and/or (c) as a part of the corona region, neutralizing the resulting Si-OH groups (a loss of micropore area and octahedral Sn4+ ions). The studies reveal that the method of preparation, n(H2O)/n(HCl) ratio and the n(Si)/n(Sn) ratio (concentration of SnCl4) of the gel significantly influence the type of tin species in the resulting Sn-SBA-15 samples. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: direct synthesis of Sn-SBA-15; Si-29 and Sn-119 MAS-NMR; Sn-mossbauer spectroscopic studies; Sn-SBA-15; tin-mesoporous silica

Strain improvement and up scaling of phytase production by aspergillus niger NCIM 563 under submerged fermentation conditions - Shah, P.; Bhavsar, Kavita P.; Soni, S. K.; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2009)
Combination of physical and chemical mutagenesis was used to isolate hyper secretory strains of Aspergillus niger NCIM 563 for phytase production. Phytase activity of mutant N-1 and N-79 was about 17 and 47% higher than the parent strain. In shake flask the productivity of phytase in parent, mutant N-1 and N-79 was 6,181, 7,619 and 9,523 IU/L per day, respectively. Up scaling of the fermentation from shake flask to 3 and 14 L New Brunswick fermenter was studied. After optimizing various fermentation parameters like aeration, agitation and carbon source in fermentation medium the fermentation time to achieve highest phytase activity was reduced considerably from 14 days in shake flask to 8 days in 14 L fermenter. Highest phytase activity of 80 IU/ml was obtained in 1% rice bran-3.5% glucose containing medium with aeration 0.2 vvm and agitation 550 rpm at room temperature on 8th day of fermentation. Addition of either bavistin (0.1%), penicillin (0.1%), formalin (0.2%) and sodium chloride (10%) in fermented broth were effective in retaining 100% phytase activity for 8 days at room temperature while these reagents along with methanol (50%) and ethanol (50%) confer 100% stability of phytase activity at 4A degrees C till 20 days. Among various carriers used for application of phytase in feed, wheat bran and rice bran were superior to silica and calcium carbonate. Thermo stabilization studies indicate 100% protection of phytase activity in presence of 12% skim milk at 70A degrees C, which will be useful for its spray drying.
Keywords: Agriculture residue; Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation

Combinatorial approach of statistical optimization and mutagenesis for improved production of acidic phytase by Aspergillus niger NCIM 563 under submerged fermentation condition - Bhavsar, Kavita P.; Gujar, P.; Shah, P.; Kumar, V. Ravi; Khire, Jayant Malhar (Applied Microbiology and Biotechnology, 2013)
Combination of statistical optimization and mutagenesis to isolate hypersecretory strains is studied to maximize phytase production from Aspergillus niger NCIM 563 under submerged fermentation. The overall results obtained show a remarkable 5.98-fold improvement in phytase production rates when compared to that using basal medium. Optimization of culture conditions from parent strain is studied first by the Plackett-Burman technique to evaluate the effects of 11 variables for phytase production. The results showed that glucose, MgSO4, KCl, incubation period, and MnSO4 are the most significant variables affecting enzyme production. Further optimization in these variables, using a central composite design technique, resulted in 3.74-fold increase in the yield of phytase production to 254,500 U/l when compared with the activity observed with basal media (68,000 U/l) in shake flask. Our experiments show that the phytase from A. niger NCIM 563 exhibits desirable activity in simulated gastric fluid conditions with low pH and also improved thermostability when compared to commercial phytase. The improved yield demonstrates the potential applicability of phytase enzyme as a source of phytase supplement for phosphorus nutrition and environmental protection in animal feed industry. Physical and chemical mutagenesis experiments were carried out in parallel to isolate hypersecretory mutants that could possibly further enhance the enzyme production. Using optimized media conditions of the parent strain, our results show that mutant strain A. niger NCIM 1359 increased the phytase activity by another 1.6-fold to 407,200 U/l.
Keywords: Animal feed; Aspergillus niger; Mutagenesis; Phytase; Statistical optimization